PEMBUATAN PROGRAM APLIKASI PENJUALAN DAN INVENTORI PADA TOKO SURYA JAYA - Suryana, Dio (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The goal of making Selling and Inventory Application Program on Toko SURYA JAYA is to minimalize errors on counting stocks and prices, also to record all of the transactions done. The benefit of making this Application Program is to help and to optimize the operation flow of the business. The computerization and the creation of the application program are done through several steps which are planning, analyzing, designing, and implementing. Several designing tools were used on this application program: Flowchart, Data Flow Diagram, Entity Relationship Diagram, and table intergration. MySQL is used as the database, Xampp as the connector between database and the display, Visual Basic as the programming language and display setting application. Blackbox testing dan user acceptance testing methods were used for the testing of this application.